IMF Staff papers : Volume 17 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1970)
This paper analyses possible approaches to a model of world trade and payments. Any world economic model resulting from linking national models together will inevitably have some of the characteristics of these national models. Since the national models that are to be connected are, overall, constructed so as to explain short-run variations in aggregate economic magnitudes such as economic activity, employment, and over-all price levels, the resulting world economic model will be best suited to explain short-term variations in trade and financial flows and the relationships between these flows and the policies conducted in the various countries with respect to the adjustment of demand and economic activity in the short run. Any model intended to explain the trade flows among many countries and regions must have strong microeconomic features it must be more nearly Walrasian than Keynesian. The practicability of building into a trade model the appropriate microeconomic features of this sort is, of course, a function of the size and degree of disaggregation of the model.